2007
DOI: 10.3174/ajnr.a0809
|View full text |Cite
|
Sign up to set email alerts
|

Death by Nondiagnosis: Why Emergent CT Angiography Should Not Be Done for Patients with Subarachnoid Hemorrhage

Abstract: musicians, and this increase correlated with the total duration of musical training. Although these changes may possibly be attributed to increased neuronal attenuation, increased NAA may also result from the increased size of neurons, alterations in synaptic attenuation, and changes in concentration of the other smaller metabolites under the NAA peak. In patients with impaired mathematic ability due to Gerstman syndrome or acalculia, spectroscopy demonstrated a focal decrease in NAA in the left posterior temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
31
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(33 citation statements)
references
References 7 publications
2
31
0
Order By: Relevance
“…7 This is related to the lower resolution of CTA compared with DSA. 8 In our series, of the 3 cases in which CTA was performed, results were negative in 1 case, underlining the higher accuracy of 3DRA. 3DRA and DSA are of higher resolution than CTA and are better in the detection of aneurysms and in defining the morphologic features of the aneurysm.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…7 This is related to the lower resolution of CTA compared with DSA. 8 In our series, of the 3 cases in which CTA was performed, results were negative in 1 case, underlining the higher accuracy of 3DRA. 3DRA and DSA are of higher resolution than CTA and are better in the detection of aneurysms and in defining the morphologic features of the aneurysm.…”
Section: Discussionmentioning
confidence: 47%
“…The relationship with adjacent small vessels (as in Case 1) is also likely to be more accurately delineated by conventional angiography. Work-up of SAH with CTA versus conventional angiography is a frequently debated topic and, as pointed out by Kallmes et al, 8 CTA can result in false-negative results, and 3DRA probably remains the most accurate study in these patients. Van Rooij et al 9 have also reported that very small aneurysms can be commonly detected by 3DRA despite negative findings on DSA.…”
Section: Discussionmentioning
confidence: 99%
“…This prevents the dilution factor associated with IV-CTA, thus providing better bolus characteristics and, in turn, higher-quality imaging. 6 Intra-arterial CTA (IA-CTA) has previously been described by Nojiri et al 7 in describing the morphologic features of the artery of Adamkiewitz. Understanding the challenges of imaging small vascular lesions, we describe our technique of performing IA-CTA for the delineation of small cerebrovascular pathologic conditions as well as for treatment planning.…”
mentioning
confidence: 99%
“…[2][3][4][5] A recent meta-analysis concluded that CT angiography can be used as a primary examination tool in the diagnostic work-up of patients with SAH, 6 but that conclusion has been questioned because of weaknesses of CT angiography in the detection of small aneurysms and aneurysms adjacent to the skull base. [7][8][9] Whether the imaging method used is DSA or CT angiography, the imaging must identify the source of bleeding, most commonly an aneurysm. We evaluated a large, multihospital data base to determine how practice is evolving with regard to the use of CT angiography and DSA in patients with ruptured cerebral aneurysm.…”
mentioning
confidence: 99%